Roles of heavy and light chains in IgM polymerization. - Bornemann, K D (1995)
IgM antibodies are secreted as multisubunit polymers that consist of as many as three discrete polypeptides: mu heavy chains, light (L) chains, and joining (J) chains. We wished to determine whether L chains that are required to confer secretory competence on immunoglobulin molecules must be present for IgM to polymerize--that is, for intersubunit disulfide bonds to form between mu chains. Using a L-chain-loss variant of an IgM-secreting hybridoma, we demonstrated that mu chains were efficiently polymerized independent of L chains, in a manner similar to that observed for conventional microL complexes, and that the mu polymers incorporated J chain. These mu polymers were not secreted but remained associated with the endoplasmic reticulum-resident chaperone BiP (GRP78). This finding is consistent with the endoplasmic reticulum being the subcellular site of IgM polymerization. We conclude that mu chain alone has the potential to direct the polymerization of secreted IgM, a process necessary but not sufficient for IgM to attain secretory competence.